ANALISIS KREDIT MACET PADA KOPERASI SIMPAN PINJAM “RIAS” P1 MARDIHARJO KECAMATAN PURWODADI KABUPATEN MUSI RAWAS - Dheo Rimbano (Jurnal Media Ekonomi (JURMEK), 2017)
Provision of credit facilities have a level of risk that the possibility of credit can not be billed, then it is necessary the correct credit analysis by employee cooperatives. Referred to as problem loans because the debtor has a delay in returning the credit. Bad credit should be quickly resolved to avoid greater losses. The purpose of this study is to find out how the analysis of bad loans using the method 5c on the cooperative savings and loan "RIAS" P1 Mardiharjo. The method used in this research is observation, interview, and documentation. Data analysis method used is qualitative method is a non-statistical analysis that helps in research. During 2011 up to 2015, the percentage of nonperforming loans in the "dressing and lending cooperatives" is 0.65% and 2.27%. When compared to the percentage of the maximum limit of bad loans determined by Bank Indonesia of 5%, then the performance of savings and loan cooperatives "2011-2015" is said to be good. The cause of credit in the cooperative savings and loan "riass" of which from the debtor who is likely due to his business less smooth, stuck, even bankrupt, due to the character of the debtor is less good, and or because of the lost guarantee that causes the debtor does not pay. From internal cooperatives due to human error, fictitious credit, and / or misalignment of credit analysis. From other parties due to natural disasters or can also be due to technological developments.